Improving Racial Equity in Community College: Developing a Plan, Implementing the Vision. (September 2021) - Felix, Eric R.
California policymakers passed the Student Equity Policy, requiring all community colleges to develop a "student equity plan" that identified outcome disparities for select student groups, including racial/ethnic students. Through an instrumental case study, I examined Huerta College because their equity plan stood out for its focus on addressing Latinx transfer inequity. I spent two years interviewing implementers, observing equity meetings, and collecting documents that served as artifacts of implementation. Key to equity planning was a critical mass of Latinx practitioners able to see the policy as an opportunity to tackle one of the greatest inequities on their campus, Latinx transfer. They used the implementation process to propose new projects that would support Latinx students in their journey to transfer from Huerta.